Digital Transformation of Village Finance: Web-Based SISKEUDES Design for Enhancing Transparency and Accountability in Naru Village, Bima Regency - Mawansyah, Julfikar (Journal of Intelligent Decision Support System (IDSS), 2024)
This research aims to evaluate the implementation and effectiveness of the web-based Siskeudes application in Naru Village, Bima Regency, in enhancing transparency and accountability in village financial management. The research method used is a mixed-method approach, combining qualitative and quantitative analysis. Through literature review, needs analysis, as well as system design and development, this research creates an integrated and user-friendly web-based Siskeudes prototype. System testing is conducted from unit testing to user testing, followed by pilot implementation in Naru Village and comprehensive evaluation. HR training is also a focus of the research to strengthen the village staff's capacity in operating the application effectively. The research concludes that the implementation of web-based Siskeudes is effective in enhancing transparency and accountability in village financial management, while HR training supports the optimal use of the application. Thus, this research makes a significant contribution to improving transparent and sustainable village financial governance.